What Are the Antecedents of Autonomy Supportive and Controlling Teaching Styles? - Gordeeva, Tamara O.; Sychev, Oleg A. (Voprosy obrazovaniâ, 2025)
Why do many teachers spontaneously tend to use motivating teaching styles, while others tend to use demotivating ones, what is behind them? Previous studies have examined the autonomy supportive style in sufficient detail, showing its positive consequences for student motivation, as well as their academic achievement  and well-being. Based on theories of motivation (self-determination theory, self-efficacy theory and implicit theories of intelligence), hypotheses are put forward about the role of three types of motivational variables in the teacher's preference for different types of interaction. This study was conducted to determine what stands behind the use of four teaching styles (N=391, teachers from primary and secondary schools in Russia) – autonomy support, structure, chaos and control, how they are related to the quality of their professional motivation, self-efficacy, and implicit theories of intelligence. Using structural equation modeling, the importance of autonomous motivation, as well as self-efficacy and  incremental theory of intelligence  in the preference for autonomy support and structuring teaching styles is shown. On the other hand, it is shown that controlled motivation and entity theory of intelligence lie behind the chaotic and controlling teaching styles. The results obtained are useful for predicting the effectiveness of teaching, as well as for developing recommendations and interventions aimed at improving teachers' interaction style, and supporting students’ autonomous motivation.